2014
DOI: 10.1089/acm.2013.0323
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Glucosamine and Chondroitin Supplement Use and Biomarkers of Systemic Inflammation

Abstract: These results support prior research suggesting that use of glucosamine and chondroitin is associated with reduced hsCRP and PGE2, but further work is needed to more definitively evaluate the anti-inflammatory potential of these supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 35 publications
2
31
0
9
Order By: Relevance
“…These results, suggesting that glucosamine and chondroitin have biologic effect in the colon, add further plausibility to the observed epidemiologic association between use of glucosamine/chondroitin and risk of CRC. This laboratory evidence is supported by two human observational studies and a recent small pilot randomized controlled cross‐over trial, in which we observed glucosamine/chondroitin to be associated with reduced levels of the systemic inflammatory marker, CRP. Given that inflammation has been strongly implicated in the etiology of CRC, this growing body of evidence offers a plausible biologic mechanism by which these supplements may reduce risk of CRC.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These results, suggesting that glucosamine and chondroitin have biologic effect in the colon, add further plausibility to the observed epidemiologic association between use of glucosamine/chondroitin and risk of CRC. This laboratory evidence is supported by two human observational studies and a recent small pilot randomized controlled cross‐over trial, in which we observed glucosamine/chondroitin to be associated with reduced levels of the systemic inflammatory marker, CRP. Given that inflammation has been strongly implicated in the etiology of CRC, this growing body of evidence offers a plausible biologic mechanism by which these supplements may reduce risk of CRC.…”
Section: Discussionsupporting
confidence: 68%
“…9 Here, the association was strongest for use of combined glucosamine and chondroitin (RR: 0.77), with no association observed for use of glucosamine only (RR: 0.94). This pattern of association, which has been observed in both studies of CRC 8 and inflammation, 29 suggests that it may be chondroitin or perhaps the combination of glucosamine 1 chondroitin driving the observed associations. Even so, such comparisons are exploratory in nature, given the relatively small number of persons reporting use of glucosamine alone.…”
Section: Discussionmentioning
confidence: 55%
“…Прием ГС (1500 мг/сут) и ХС (1200 мг/сут) в группе взрослых испытуемых 20-55 лет (n=18) с избыточной массой тела и ожирением (ИМТ 25-32 кг/м 2 ) в течение 28 дней приводил к падению уровня СРБ на 23% по сравнению с плацебо (р=0,048) [12]. В другом исследовании прием ГС + ХС сопровождался снижением абнормально повышенных уровней СРБ на 28-36% и окислительного стресса на 40-47% (n=220) [14]. В популяционном исследовании, включавшем 10 000 взрослых пациентов, регулярное использование ГС + ХС также было ассоциировано со снижением уровня СРБ (на 20%) [15].…”
Section: та р г е т н ы е б е л к и п о с р е д с т в о м к о т о рunclassified
“…Активация под влиянием ХС ре-цептора CD44 снижает избыточную активность матриксных металлопроте-иназ (ММР) за счет регулирования транскрипции генов [5], способствует повышению активности хондроитин-сульфатных гликозилтрансфераз CHPF, CSGALNACT1, CSGALNACT2 (реконструкция соединительной тка-ни) [6], снижению активации NF-кВ провоспалительных цитокинов интер-лейкина (ИЛ) 1, 6, фактора некроза опухолей α (ФНОα) и СРБ [7][8][9][10][11][12][13].…”
Section: молекулярные эффекты хондрогарда при остеоартрите и грыжах мunclassified
“…М о л е к у л я р н ы е м е х а н и з м ы п р о т и в о в о с п а л и т е л ь н о г о э ф ф е к т а Х С ХС снижают активацию NF-кВ и биомаркеров воспа-ления ИЛ1, ИЛ6 и СРБ [7]. Прием ХС (1200 мг/сут) и ГС (1500 мг/сут), согласно данным исследования группы здо-ровых добровольцев с повышенным индексом массы тела (25-32 кг/м 2 , n=18, 20-55 лет), в течение 28 дней приводил к снижению содержания СРБ на 23% по сравнению с плаце-бо (р=0,048) [8], а по данным другого исследования [9], -на 28-36% (n=220). В исследовании, включавшем 10 000 взрослых здоровых добровольцев, регулярное использова-ние ХС + ГС было связано с уменьшением уровня СРБ (на 20%) [10].…”
Section: молекулярные эффекты хондрогарда при остеоартрите и грыжах мunclassified